Needs and Profile of Game Temanggung Library (GATEL) for Madrasah Ibtidaiyah in Temanggung Regency: A Preliminary Study - Hamidulloh Ibda; Putri Maharani, Shevia; Milata Zakia, Kuni (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2023)
This research-based community service aims to analyze the overview and media needs of Game Temanggung Library (GATEL) in Madrasah Ibtidaiyah in Temanggung Regency by applying a survey method with a cross-sectional survey type and in-depth interviews. The findings in this article refer to ten criteria. First, 100% of Madrasah Ibtidaiyah in the assisted subjects have no games for learning. Second, not having games is because there is no training, ignorance, and unfamiliarity with games. Third, there has never been training on making games in all Madrasah Ibtidaiyah in the assisted subjects. Fourth, the condition of Madrasah Ibtidaiyah students in the assisted subjects in playing games, data obtained 60% Madrasah Ibtidaiyah often, 40% Madrasah Ibtidaiyah ever, and 0% Madrasah Ibtidaiyah never. Fifth, the condition of the names of games/types played by students in the assisted subjects is very diverse, namely LoL games, Jigsaw Puzzles games, E-Sport, LEGO Nijago, and Once Upon a Tower. Sixth, the condition of the games played by students in the assisted subjects integrated into learning obtained data very often 0%, quite often 0%, and less often as much as 100%. Seventh, the causes of students playing games without being directed and not integrated into learning is obtained because the teacher cannot direct and there is no planning, no assistance, lack of concern, not accompanied by parents and teachers, and not noticed by the teacher. Eighth, the condition of teacher knowledge in the assisted subjects on educational games obtained data that 80% know and 20% do not. Ninth, the condition of Madrasah Ibtidaiyah teachers' knowledge on the assisted subjects of Homer, Prodigy Math, Buzzmath, Robot School, PBS Kids, The Time Tribe, and One Globe Kids games obtained data of 20% of teachers know, and 80% of teachers do not know. The last aspect is that all assisted subjects provided input on the need for training because there has rarely been training or training in making games.